UPAYA PENCEGAHAN STUNTING PADA BALITA (LITERATURE REVIEW) STUNTING PREVENTION EFFORTS IN TODDLERS - Sri Mulia Astuti; Suryani, Lilis; Putri, Dea Ananda Putri; Arsyad, Jihan Fadilla (Balai Besar Pelatihan Kesehatan (BBPK) Makassar, 2023)
Stunting is a chronic malnutrition problem caused by chronic lack of nutritional intake. Many factors cause stunting, namely low socioeconomic status, food insecurity, nutritional status of mothers during pregnancy, low birth weight, parenting, nutritional status, sanitation and water availability. This study aims to determine how to prevent stunting in toddlers. Methods, this review is carried out in stages: determining PICO questions (Problem, Intervention, Comparison, Outcome), case control, article search, assessment of relevant articles, and article analysis and synthesis. Relevant articles are searched through an electronic database, namely Google Scholar using the keyword